Two-dimensional molybdenum trioxide nanoflakes wrapped with interlayer-expanded molybdenum disulfide nanosheets: Superior performances in supercapacitive energy storage and visible-light-driven photocatalysis. (11th October 2021) - Sharma, Krishna Hari; Hang, Da-Ren; Bolloju, Satish; Lee, Jyh-Tsung; Wu, Hui-Fen; Islam, Sk Emdadul; Chou, Mitch M.C.; Liang, Chi-Te; Srivastava, Rupesh Rohan
Abstract: Two-dimensional layered molybdenum disulfide and molybdenum trioxide ( α -MoO3 ) have fascinating potential for complementary energy storage and conversion applications due to their high surface area and multiple oxidation states of Mo. We report a novel hierarchical 1T/2H MoS2 /MoO3 nanocomposite prepared by a scalable liquid-phase exfoliation and subsequent facile hydrothermal route. The growth of MoS2 onto 2D α -MoO3 creates a unique 2D/2D hierarchical structure, which reduces the aggregation of α -MoO3 nanoflakes, improves the electrical conductivity of the composite electrode, and activates inert basal plane of MoS2 . The electrochemical measurements revealed that such a composite possessed higher specific capacitance and promoted capacitance retention in a symmetric supercapacitor assembly. The remarkably enhanced visible-light-driven photocatalytic performance of hybrid hierarchical architecture can be attributed to a few distinctive synergistic effects, including activated inert basal plane, facilitated interfacial charge transfer, and peculiar ultrathin nanosheet framework with a large surface area and high content of exposed edge sites. Highlights: Facile synthesis of bifunctional hierarchical 1T/2H MoS2 /MoO3 nanocomposite. The nanocomposite exhibits excellent visible-light-driven catalytic performance. The nanocomposite shows superior charge retention and higher specific capacitance. The phase engineering of MoS2 boosts energy conversion and storage performance. A mechanism for enhanced photocatalytic performance was proposed.